Modal Analysis of Dissimilar Plate Metal Joining with Different Thicknesses using MIG Welding - M. M., Hatifi; M. H., Firdaus; A. R., Yusoff (Universiti Malaysia Pahang, 2014)
This paper presents a study of the dynamic behavior of joining hybrid parts, stainless steel and aluminum alloy, by MIG welding. The objective is to analyze the effect of welding on dissimilar plates of stainless steel and aluminum. A finite element model of joining stainless steel and aluminum alloy by welding was built using a structural threedimensional (3D) solid modeling element. Impact testing using hammer excitation and accelerometer response measuring techniques was conducted to measure the vibration properties of the hybrid parts. The natural frequency and the mode shape graph from experimental modal analysis were then compared with the results that were obtained from finite elements (FE) and showed good agreement. Joining welding gives effect to dynamic properties (mode shape) of modal analysis, especially mode 1,3 (bending pattern) and mode 4 (second twisting). The results show significant points about the effect of MIG welding of dissimilar plate in terms of their dynamic properties compared to welding of the same material. Through comparison of the simulation results and the experimental measurements, it can be assumed that, besides the welding-brazing process, other key manufacturing processes such as cladding, buttering and heat treatment should also be taken into account to accurately predict the dynamic properties in the whole range of dissimilar metal joining.